2007
DOI: 10.1089/end.2006.0411
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Pyeloplasty Compared with Open Pyeloplasty in Children

Abstract: The benefits of laparoscopic pyeloplasty include a high reproducible success rate comparable to the results achieved by open pyeloplasty. Our results indicate minimal morbidity such as pain and a quick return to normal activities. The hospital stay is significantly reduced, although the operative times are long compared with open pyeloplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 19 publications
3
24
0
Order By: Relevance
“…However, to date, only few comparative paediatric studies of conventional laparoscopic and open pyeloplasties have been reported. [5][6][7][8][9] Analysing these reports, laparoscopy is associated with shorter hospital stay, less narcotic use and less pain. On the other hand, laparoscopic pyeloplasty implies a longer operative time and seems associated with more urinary leaks.…”
Section: Discussionmentioning
confidence: 99%
“…However, to date, only few comparative paediatric studies of conventional laparoscopic and open pyeloplasties have been reported. [5][6][7][8][9] Analysing these reports, laparoscopy is associated with shorter hospital stay, less narcotic use and less pain. On the other hand, laparoscopic pyeloplasty implies a longer operative time and seems associated with more urinary leaks.…”
Section: Discussionmentioning
confidence: 99%
“…Ravish et al [12] prospectively compared the results of laparoscopic and open pyeloplasty in children with UPJ obstruction. They concluded that the benefits of laparoscopic pyeloplasty included a high reproducible success rate comparable to the results achieved by open pyeloplasty.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several disadvantages of LP have been pointed out in different reports. The disadvantage of LP is that operative times are significantly higher than open pyeloplasty 11,12 . In particular, laparoscopic suturing particularly for children is challenging and time-consuming and requires a learning curve 11 , however, it significantly improved, even with pediatric LP, with increased experience in previous reports 11,13 .Open pyeloplasty is performed through the retroperitoneal approach, which has the advantage of less risk of intraperitoneal organ injury, postoperative ileus, and avoidance of potential deleterious effects of peritoneal exposure to blood and urine.…”
Section: Discussionmentioning
confidence: 99%